Infliximab associated with life-threatening lung infection in a patient with Behcet disease with intestinal and hematopoietic system involvement: A case report - Chen, Yong (Medicine (Baltimore), 2017)
RATIONALE: Tumor necrosis factor (TNF-α) participates in the pathophysiology of Behcet's disease (BD) and myelodysplastic syndrome (MDS). Infliximab is recommaned for the most severe type of BD, however, there is little evidence for its effectiveness in BD associated MDS. PATIENT CONCERNS: A 46-year-old female, initially diagnosed with intestinal BD and leukopenia was later diagnosed as MDS. Treatement with infliximab and other immunoregulators lead to life-threatening pneumonia. DIAGNOSIS: Intestinal BD associated with MDS involving trisomy 8. INTERVENTIONS: The patient initially treated with methylprednisolone, thalidomide, cyclosporine A, and infliximab, which lead to severe lung infection. Therefore, the patient was transferred to Intensive Care Unit for life supportive, anti-infection and immune improving therapy. OUTCOMES: The patient survived from the lung infection. With combination of methylprednisolone, thalidomide and cyclosporine A, the patient recovered from her intestinal ulceration and MDS manifestations. LESSONS: Infliximab treatment may not benefit a patient with BD associated with MDS but place the patient at risk of infection.